Antecedents of recommendation and repurchase intention on medical tourism - Ari Prasetyo, Hendarjatno, Sedianingsih, Ririn Tri Ratnasari, (Opción, 2019)
The aim of the study is to investigate the antecedents of recommendation and repurchase intention on medical tourism. The research method that was used is represented in quantitative surveys and in-depth results using in-depth interviews. As a result, health care and the intention to reuse health services are the quality of medical services for patients, medical equipment technology, hospital management, price and benefit comparisons, and communication. In conclusion, health services and communication does not affect the intention to recommend health services.